Principles of Islamic Law and the methods of interpretation of the texts (Uṣūl al-Fiqh) - Kayadibi, Saim (Islamic Book Trust (IBT), 2017)
The book in your hand, Principles of Islamic Law and Methods of the Interpretation of the Texts (Uṣūl al-Fiqh), is aimed to help students, lawyers and people intererested in the study of Islamic law to understand the field comprehensively. This work is, indeed, a comprehensive study in its field, authored in a clear and simple manner that meets the requirements of a needed textbook on principles of Islamic jurisprudence (uṣūl al-fiqh), and consisting of six chapters, including an introductory chapter. Chapter one, the introductory chapter, highlights the development of the principles of Islamic law and the three distinct approaches of the formulation of uṣūl al-fiqh. It also gives the definitions of uṣūl al-fiqh, explains the ḥukm shar‘ī with its essential terms related to uṣūl al-fiqh, the Sharī‘ah and its components dealing with al-aḥkām al-i‘tiqādiyyah (rulings related to beliefs), al-aḥkām al-khuluqiyyah (rulings related to moral and ethics) and al-aḥkām al-‘amaliyyah (rulings related to the sayings and doings of the individuals and their relationships with others). The chapter also deals with the characteristics of the Sharī‘ah; differences between mujtahid and faqīh, ijtihād and taqlīd, muqallid and faqīh, qawā‘id al-fiqhiyyah and uṣūl al-fiqh; and the meaning of adillah. Chapter two is devoted to the sources of Islamic law, classifying them into two types, as unanimously accepted sources (the primary sources), such as the Qur’ān, the Sunnah, ijmā‘, (consensus) and qiyās (analogy); the controversial sources (the secondary sources), such as istiḥsān (juristic preference), maṣlaḥah mursalah (public interest) or al-istiṣlāḥ, istiṣḥāb (presumption of continuity), qawl al-ṣaḥābī (the sayings of a Companion of the Prophet (pbuh)), ‘urf (custom), sadd al-dharā’i‘ (blocking the means), shar‘ man qablanā (revealed laws preceding the sharī‘ah of Islam) and istiqrā’ (induction).